Detraction in game immersion experiences in social tabletop role-playing games - Wan Jaafar, Wan Munira; Tai, Liang Kwang (Faculty of Human Ecology, Universiti Putra Malaysia, 2022)
Previous attempts to test and measure immersion cognition in social gaming has resulted in mixed results, especially in non-digital social games such as table-top role-playing games (TRPGs). This study seeks to instead investigate the problems of social-immersion in TRPGs through detraction elements and counter-immersive gaming experiences. A thematic analysis amongst focus group discussions amongst TRPG gamers from the Klang Valley region is conducted to investigate the detraction phenomenon. Several key game design topics and behaviours related to the detraction experience have been identified. This study findings suggest detraction as a correlational factor to the overall social-immersive experiences in TRPGs and recommends further research around the subject matter.